Empty fruit bunch (EFB) gasification in an entrained flow gasification system - Wan Muhamad Syafiq, Wan Ismail; Ruwaida, Abdul Rasid (Bangladesh University of Engineering and Technology, 2017)
Biomass has become one of the most commonly used renewable sources of energy in the last two decades. Empty fruit bunch (EFB) is one of the examples for the biomass that is used as a renewable energy source. From the palm oil processing industry, only 10% are the final products such as palm oil and palm kernel oil, while the remaining 90% are harvestable biomass waste in the form of EFB, palm kernel shell (PKS) and oil palm frond (OPF). This overload amount of biomass waste will cause an abundance of waste which will also affect the environment. To convert EFB into usable energy in ways that are more efficient, less polluting, and economical, gasification has merge as one of the most favorable technological innovations in synthesis gas (syngas) production. The main aim of this work is to study the EFB gasification in an entrained flow gasification process based on the different operating temperature (700°C to 900°C) and equivalence ratio, ER (0.2 – 0.4), evaluated based on the production of gases such as hydrogen (H2), carbon monoxide (CO), carbon dioxide (CO2) and methane (CH4). It was found that as the temperature was increased from 700°C to 900°C, the production of H2 and CO2 increased while CO was decreased. The optimum ER value of 0.30 was found to attain the highest Cold Gas Efficiency (CGE) value of 74.03% at 900°C.